2008
DOI: 10.1097/olq.0b013e31816907fa
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Risk Factors for Bacterial Vaginosis in HIV-1-Seronegative African Women

Abstract: Vaginal washing and unprotected intercourse were associated with increased risk of BV. These findings could help to inform the development of novel vaginal health approaches for HIV-1 risk reduction in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 29 publications
8
58
1
Order By: Relevance
“…For this substudy, we recruited women who reported vaginal washing beyond the introitus within the last month. In addition, women were required to be sexually active, non-pregnant, not within the first 3 months post partum, and not on hormonal contraception or, alternatively, on stable hormonal contraception for ≥2 months 10 18. The study was approved by ethical committees at the Kenyatta National Hospital and the University of Washington.…”
Section: Methodsmentioning
confidence: 99%
“…For this substudy, we recruited women who reported vaginal washing beyond the introitus within the last month. In addition, women were required to be sexually active, non-pregnant, not within the first 3 months post partum, and not on hormonal contraception or, alternatively, on stable hormonal contraception for ≥2 months 10 18. The study was approved by ethical committees at the Kenyatta National Hospital and the University of Washington.…”
Section: Methodsmentioning
confidence: 99%
“…According to some researchers [43,44,46], the higher recurrence rate among patients who use condoms irregularly and have multiple partners reinforces the hypothesis of sexual ISRN Infectious Diseases 5 BV transmission. However, Bradshaw et al [40] observed a higher recurrence of the infection among non HIV-infected women with a steady partner, as it was observed in the present study on HIV-infected women.…”
Section: Discussionmentioning
confidence: 89%
“…e rate of hormonal contraceptive use, considered to be a protective factor against BV [39,40,44], was low (10.4%) in the studied sample; however, it was not related to higher persistence/recurrence, probably due to the small number of patients involved. Nevertheless, there was an association between BV persistence/recurrence and postmenopause ( 0.0 ), and none of the patients had hormonal replacement.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings concur with our earlier qualitative study [20], which also found the majority of women felt sexual activity triggered BV onset, the main triggers including unprotected sex and sex with a new male partner. Epidemiological data strongly supports women's experiences of the sexual triggers for BV, with studies commonly finding an association between an increased risk of BV and inconsistent or lack of condom use or a new sexual partner [2,17,[51][52][53][54][55]. To a lesser extent, lifestyle triggering factors nominated by women, such as psychosocial stress, have also been associated with an increased risk of BV [39,56].…”
Section: Discussionmentioning
confidence: 93%